Assessing the status of the Barotse floodplain fishery and the implications of Australian redclaw crayfish Cherax quadricarinatus invasion on the fishery - Nawa, Nawa (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
Inland capture fisheries play an important role of supporting livelihoods of people in developing countries. Despite their significance these fisheries are often poorly monitored resulting in them being undervalued and often missing from policy and decision-making relating to food security and water use, particularly in third world countries. The Anthropocene has given rise to increased pressure on these systems, further justifying the need for monitoring activities to determine the ecosystem service provision status and the levels of existing and emerging threats to such services. This thesis focuses on the Barotse floodplain fishery of the Upper Zambezi system and the potential implications of the recent Cherax quadricarinatus invasion on the floodplain fishery. The thesis specifically assesses the current status of the fishery (Chapter 3), invasion dynamics of C. quadricarinatus (Chapter 4), economic impact of C. quadricarinatus on the fishery (Chapter 5) and fishers' knowledge, awareness and perception of C. quadricarinatus (Chapter 6). To evaluate the current status of the fishery (Chapter 3), fisheries dependant surveys were conducted. The study revealed a multi-gear multi-species fishery with average catch rates of 5.83 kg per fisher per day and estimated annual harvest of 3123 tonnes per annum. The decline in catch rate, low mean sizes of species harvested, change in species composition, and predominant use of illegal fishing gear compared to previous surveys, suggested further overexploitation of fishery resources. The invasive C. quadricarinatus was identified as the most dominant by-catch species and more prevalent among fishers at the invasion core and in dry season. Analysis of the invasion dynamics of C. quadricarinatus (Chapter 4) involved extensive survey of the Barotse floodplain using collapsible promar traps. The study revealed significant up and down-stream spread from the 2019 range on the floodplain. Relative abundance was higher at the invasion core compared to the invasion edge while male to female sex ratio was not different between these zones, implying both sexes were acting as dispersers. Signals of environmental filtering were not detected while density dependent spatial sorting, and hydrological variation had a strong influence on C. quadricarinatus spread. To quantify economic impact C. quadricarinatus (Chapter 5) creel surveys were conducted during wet and dry season across the invasion range. The study showed that fish damage due to crayfish was limited to gillnets at the invasion core during the dry season and equated to the monetary loss of ~ US$ 21,000 per annum. In addition, gear damage and loss of time due to crayfish was experienced for various fishing gears but most prevalent at the invasion core and more so in dry season. Assessment of fishers' awareness, knowledge and perception (Chapter 6) involved the use of social surveys administered at the invasion core. This component revealed that most of the respondents were aware of, but not knowledgeable about C. quadricarinatus. Respondents were not aware of any management information relating to C. quadricarinatus and consequently did not follow any management practices. The respondents were supportive of management interventions due to their perceived threat of C. quadricarinatus to the fishery. Age, education, and residence of respondents significantly influenced knowledge and perceptions of C. quadricarinatus. Findings from this study have important implications for the conservation of floodplain wetlands as it informs policy makers to put in place measures that address both overexploitation and aquatic invasive species dynamics to better facilitate sustainability of fisheries and conservation of biodiversity.
Keywords: Zambezi Floodplains; Fishery resources Zambia Barotse Flood Plain; Introduced fishes Economic aspects; Cherax quadricarinatus; Fishery management